SIKLUS PENGENDAPAN KUARTER BERBASIS KARAKTERISTIK PERUBAHAN MUKA LAUT DI LEMBAH KRUENG ACEH, ACEH BESAR, PROVINSI NANGROE ACEH DARUSSALAM - -, Herman Moechtar; -, Zulfiadi Zakaria (Bulletin of Scientific Contribution, 2010)
Studies of the Quaternary depositional cycles based on character of sea-level changes in the Krueng Aceh Valley ( Aceh Besar), revealed seven of depositional fasies. These depositional fasies consist of beach/ beach ridges (Fep/ Fepp), nearshore (Feldp), offshore (Fellp), river channel (Feas), floodplain (Fedb), swamp (Fer), and marsh (Ferb) deposits. Based on correlation of the lateral and vertical variation of the Quaternary deposits, four Interval of depositional facies (IFP A-D) occurred. Each of depositional facies is, characterized by variation of the depositional environment alternating which is controlled by sea-level changes under influenced by climate circulation and tectonic. Probably, the character of each depositional interval could be called as cycle of five ordo of sea level changes which correlated with Milankovitch cycle of 20,000 years.The study was based on analyses of sedimentology and stratigraphy of nine borehole informations, and the penetration of the bore head varied from 51,50 to 125 m. Three stratigraphical cross section have been correlated, that is BD2 – BD8, BD2 – BD5, and BD8 – BD5 cross sections.